THE IMPORTANCE OF FOOTBALL IN THE SYSTEM OF PHYSICAL EDUCATION: PEDAGOGICAL ASPECTS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article is devoted to the consideration of theoretical and practical issues related to the implementation of additional general education programs in the field of physical culture and sports development based on the use of popular sports activities, including football. In the course of the study, the authors conclude that football, as a type of sports game, should be used as part of the compulsory school curriculum for physical education.